Childhood and Youth of Adrienne von Speyr (1902-1967): A Case Study of Giftedness - Paweł Kaźmierczak (Ignatianum University Press, 2022)
The aim of this paper is to explore the unique giftedness of the Swiss physician and mystic Adrienne von Speyr (1902-1967) during her childhood and youth. The following research issues are addressed: 1) the research method and biographical sources on von Speyr, 2) a holistic portrait of her, 3) her early years, 4) the three-ring conception of giftedness as a fitting theoretical framework, and 5) an exploration of Adrienne's case using Renzulli's three-ring concept. Case study based on a content analysis of biographical sources was the adopted research method. The context of the research is interest in Adrienne von Speyr as a woman endowed with unique qualities and a unique mission in the Church. This general interest inspired the research into her childhood and youth, when some of these qualities were already present. The argumentation process involved analyzing sources and citing content relevant to the theoretical framework. The research confirms von Speyr's giftedness in her childhood and youth and delineates its characteristics. We can conclude that her early talents and gifts are in themselves worthy of interest and that they may inspire further research on her life and work in general.